Virtual reconstruction of pelvic tumor defects based on a gender-specific statistical shape model. (14th March 2013) - Krol, Zdzislaw; Skadlubowicz, Pawel; Hefti, Fritz; Krieg, Andreas H.
Abstract : Tumors in the pelvic region cause deformation and destruction of bony structures. Because the original pelvic anatomy cannot be adequately assessed at the tumor site, reconstruction with patient-specific implants is required. A widely used strategy for the reconstructive planning is mirroring of the contralateral side. We analyzed the statistical shape model (SSM)-based reconstruction method and compared it with the mirroring approach. Our approach used a gender-specific pelvic SSM ( n = 50 for each gender) to generate implant geometries. The main objectives of this study were to analyze and evaluate the virtual anatomical reconstruction of eight tumor-damaged pelvic bones using the SSM approach. We achieved an overall mean deviation distance of 0.89 mm and 1.26 mm for the reconstruction of the equivalent defect in the healthy hemipelvis. Quantitative comparison with the mirroring method showed that the SSM-based reconstruction method reconstructs the defect with the same clinically acceptable accuracy as the mirroring method. The study demonstrates that the presented model can be a valuable tool for the planning of pelvic reconstructive surgery and implant design.